IMPROVING STUDENTS’ VOCABULARY ACHIEVEMENT IN READING RECOUNT TEXT THROUGH ANAGRAM TECHNIQUE - Maimunah and Bachtiar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study concerns with improving students vocabulary achievement in reading recount text through anagram technique. The objective was to investigate improvement of students’ achievement in vocabulary by applying anagram technique. This research was conducted by using action research method. The subject of the study was grade VIII students of SMP SWASTA PEMBANGUNAN GALANG totalling to 29 students. They were taught vocabulary by anagram technique. The instruments for collecting data were quantitative data and qualitative data (observation sheet and questionnaire sheet). Based on the test score of quantitative data, students’ score kept improving in every evaluation. In the orientation test the mean was 43, 2, in the cycle I test the mean was 55, 6. In the cycle II test the mean was 67.2. The percentage of orientation test was 10, 34%, cycle I test was 24, 13% and cycle II test was 86, 20%. The finding of the research showed that applying anagram technique significantly improved students’ vocabulary achievement. The qualitative data show that the students were more interested and motivated on vocabulary achievement through anagram. It is suggested that teachers should apply anagram technique as one of methods to improve students’ achievement in vocabulary.